Viterbi optimization for crime detection and identification - Reem Razzaq Abdul Hussain; Salih Mahdi Al-Qaraawi; Muayad Sadik Croock (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this paper, we introduce two types of hybridization. The first contribution is the hybridization between the Viterbi algorithm and Baum Welch in order to predict crime locations. While the second contribution considers the optimization based on decision tree (DT) in combination with the Viterbi algorithm for criminal identification using Iraq and India crime dataset. This work is based on our previous work [1]. The main goal is to enhance the results of the model in both consuming times and to get a more accurate model. The obtained results proved the achievement of both goals in an efficient way.